Management of the Patient Candidate to Prosthetic Implant Solution - Norina Forna; Iulian Costin Lupu (Romanian Society of Oral Rehabilitation, 2012)
The success of any therapeutic solutions is based on psychological training and motivation of the patient. Nowadays, the dentist who uses a prosthetic implant solution has at hand a series of laboratory tests using various radiological software that provides more accurate images. This software that is used at digital radiographs, CT, also allows simulations of the number, the implant positioning, etc. and helps the clinician to explain to the patient the therapeutic solution, the complexity of the dental work, and the need for continuous supervision after the surgery itself.